Management of Pundu Nence as Mountain Tourism in Bima City: A Model of Visitor Management Approach - Herman Herman; Rumba Rumba; Anak Agung Ngurah Sedana Putra; Putu Ari Nugraha (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2023)
Purpose: Mountain tourism being a tourist destination that offers natural and special interest attractions thus appropriate for visitors that prefer nature and adventure. Understanding visitor management is crucial for mountain tourism operators. The aims of this study are to 1) Identify the availability of tourist attractions; 2) Identify the actual condition of visitor management; and 3) Recommend a management quality improvement model through the visitor management approach. Method: The research applied a qualitative approach and employed interviews and observations to collect data. The research was conducted in the Mount Pundu Nence area. This research was conducted from January to March 2023. Result: The results of the study indicated that the component of tourist attractions consists of interest as the main attraction and is supported by natural and cultural attractions. The actual condition of visitor management is not well demonstrated by the unidentified registration of visitors, unavailable tourist information center (TIC), the visitor flow is incomplete, the pricing and fees are less than optimal, the parking lot is not adequate, the signboard is lacking and the waste management is not optimal. The research recommended a management improvement model based on the components of hard visitor management tools and soft visitor management tools. The hard visitor management tools recommended three aspects, such as setting prices and fees in the packaging of packages, providing parking space and creating regulations for waste management. The soft visitor management tools recommended four aspects, i.e., using QR code as a registration and payment system for visitors, providing tourist information center (TIC) by utilizing the current buildings and using social media to manage information, installing signage in vital areas, and developing a visitor flow system that could be implemented by visitors and operators. Contribution: The research presents a model of mountain tourism management using the visitor management approach. The model could be implemented by tourism operators or local authorities to improve the quality of mountain tourism experiences.